Identification of host and viral factors involved in a dissimilar resolution of a hepatitis C virus infection. (20th November 2013) - Cubero, Maria; Gregori, Josep; Esteban, Juan I.; García‐Cehic, Damir; Bes, Marta; Perales, Celia; Domingo, Esteban; Rodríguez‐Frías, Francisco; Sauleda, Silvia; Casillas, Rosario; Sanchez, Alex; Ortega, Israel; et al.
Abstract Background & Aims Hepatitis C virus (HCV) transmission from a chronic patient to a susceptible individual is a good opportunity to study viral and host factors that may influence the natural course of hepatitis C infection towards either spontaneous recovery or chronicity. To compare a documented case of a bottleneck event in the sexual transmission of HCV from a chronically infected patient to a recipient host that cleared infection. Methods Host genetic components such as Class I and II HLA and IL28B polymorphism (rs12979860 SNPs) were identified by direct sequencing and LightMix analysis, respectively. Deep nucleotide sequence analysis of quasispecies complexity was performed using massive pyrosequencing platform (454 GS‐FLX), and the CD4 specific immune response was characterized by ELISPOT. Results and Conclusions Sequencing analysis and CD4 response highlighted several NS3‐helicase domains in which an interplay between amino acid variability and CD4 immune response might have contributed either to chronicity in the donor patient or to viral clearance in the receptor (newly infected) patient.